Guidebook for environmental and natural resources accounting methods and procedures. - Philippines. Department of Environment and Natural Resources ([Quezon City] Department of Environment and Natural Resources, 1993)
A manual on resource accounting to aid policymakers, students, researchers and advocates for Philippine natural resources. Includes definition of terms, physical account procedures, valuation methods, data requirements and sample computations. Also refer to "Guide to Environmental Accounting and Policy Development: The ENRAP Experience" for a more detailed explanation of the framework and policy applications governing this work.
At head of title: Philippine Environmental and Natural Resources Accounting Project (ENRAP).
Prepared for the Department of Environment and Natural Resources by the International Resources Group in association with Edgevale Associates and the Resources, Environment and Economics Center for Studies, Inc. under contract no. 492-0465-C-00-4042-00 with the United States Agency for International Development (USAID/Philippines).
Keywords: Environmental auditing -- Philippines -- Handbooks, manuals, etc; Natural resources -- Accounting. -- Philippines